A Framework for Integrating Water Projects in Disaster Reconstruction Processes in the International Context. (October 2015) - Juran, Luke
Water projects triggered by disaster reconstruction processes are inherently unique and warrant a specialized approach. Thus, the objective of this article is to guide reconstruction actors toward the establishment of more culturally and environmentally sensitive water arrangements by providing a framework of key points to consider. Water infrastructure introduced after disasters differs from "normal" water infrastructure in several distinct ways: nature and needs of the subjects, expectations of recovery and rehabilitation, scale, funding and organizational structure, resettlement, and temporal constraints. Acknowledging these differences, a framework is presented to more aptly manage water sector reconstruction. The framework—informed by fieldwork in post-tsunami South India, the literature, and gaps therein—seeks to minimize project failures that have surfaced across space, time, and disaster.